การจัดกิจกรรมการเรียนรู้ด้วยชุดกิจกรรมรายวิชารัฐและสังคม ในการพัฒนา (เสริมสร้าง) ทักษะสมองเพื่อความสำเร็จของนักศึกษา - วารุณี ณ นคร (มหาวิทยาลัยสงขลานครินทร์ วิทยาเขตปัตตานี, 2024)
The Classroom Action Research on "Activity - Based Learning Management from Activity in the Subject of State and Society for Promoting Executive Function Skill for Political Sciences Students is to learn how to Executive Functions (EF), crucial ability in a century that is changing quickly and is highly disruption for the living and working worlds. The study's two goals were to examine undergraduate students' cognitive capacities as well as their brain talents for effectiveness in planning and arranging learning activities with the state and social learning activity package. Students' satisfaction with the provided activities. It employs the ideas of thinking skills for a successful life and teaching and learning in the twenty-first century as its two main conceptual frameworks for education. This research is participatory action research (PAR) and gather information through both quantitative and qualitative research. 146 students are drawn from the target group in the first semester academic year 2020 The study found that the target group had developed Executive Functions (EF) higher than before participating in the activity with statistical significance in both overall and individual skills in all 9 items. That participating in activities can enable oneself to develop Executive Functions (EF) in each dimension. Additionally, the conclusions are students can review their learning by employing a selection of exercises during the learning process increased review and reflection of your own knowledge and abilities which approaches or abilities are one's own creations. This enables the target group to apply the aforementioned learning strategies in the future to further build their own skills and encourage students to learning more about themselves. It was discovered that giving students the opportunity to build more self-learning abilities, such as responsibility, is one of the requirements for developing learners' EF skills through Zoom Meeting. This suggests that organizing a variety of learning activities and deliberately concentrating on the development of learners' skills might increase the efficacy of learning through online channels. By allowing students to actively participate in their education and by fostering a laid-back, adaptable learning atmosphere, instructors can encourage independent study outside of the classroom.